Study of the reliability of quartz resonators in miniature ceramic packages - M. I. Boychuk; V. E. Krivonogov; S. A. Mikaeva; L. A. Vasilieva (Российский технологический журнал, 2022)
Objectives. In the development of radio electronics and communications, it is important that the requirements for the reliability, stability of the generated frequencies, and selectivity of the receiving equipment are fulfilled. The use of quartz resonators, widely used in radio circuits today, has partially allowed for the reliability of communication devices and guaranteed high frequency stability to be enhanced without complicating the circuit. Modern global trends in the development of electrical equipment are associated with miniaturization. The dimensions of quartz resonators are decreasing every year, while the requirements for reliability remain high. The study aimed to evaluate the possibility of using quartz resonators packaged in a miniature ceramic case 2.5 × 2.0 × 0.6 mm, under conditions of elevated ambient temperature. It has also allowed for the development of optimal requirements for the thermal training regime as the basic technological operation for stabilizing the oscillation frequency.Methods. Reliability testing of quartz resonators and methods of statistical modeling in radio engineering.Results. The results established the requirements for the reliability of RK588 quartz resonators in miniature ceramic cases 2.5 × 2.0 × 0.6 mm in size under the influence of elevated ambient temperatures of +85 °C and +125 °C. The requirements for frequency drift when exposed to elevated ambient temperature on the crystalline plate type based on RF patent No. 27122426 “Method of manufacturing thin crystalline plates and thin crystalline elements” were also specified. The method of thermal training was optimized and the ageing coefficients were established.Conclusions. The coefficients of ageing calculated for the resonators during the reliability tests was as follows: Batch No. 1 at a temperature of +85 °C was 0.75; and for Batch No. 2 at a temperature of +125 °C was 0.18. For this type of piezoelectric element with a size of 1.5 × 1.0 mm at an operating temperature of +125 °C the ageing coefficient is 4 times lower than at a temperature of +85 °C. This indicates the possibility of using the RK588 resonator at elevated ambient temperatures.